The Role Analysis of Waste Bank in Improving the Community's Creative Economy (Study at Ketumbar Pamulang Waste Bank) - Gunartin Gunartin; Edi Mulyanto; Denok Sunarsi (Budapest International Research and Critics University, 2020)
The research objective with the title